Стихотворения. 1813-1825 - Пушкин Александр Сергеевич (Библиотека "Огонек", 1954)
Экземпляры: КХ (20110804) / Инвентарный номер: 167954 / Цена: 0.90 / Сис.шифр: Р1 / Авт.знак: П 91 / ГРНТИ: 17 / ББК: 84(2=411.2)-5